Accurately quantifying the shape of birds' eggs. Issue 19 (5th September 2018) - Biggins, John D.; Thompson, Jamie E.; Birkhead, Tim R.
Abstract: Describing the range of avian egg shapes quantitatively has long been recognized as difficult. A variety of approaches has been adopted, some of which aim to capture the shape accurately and some to provide intelligible indices of shape. The objectives here are to show that a (four‐parameter) method proposed by Preston (1953, The Auk, 70, 160) is the best option for quantifying egg shape, to provide and document an R program for applying this method to suitable photographs of eggs, to illustrate that intelligible shape indices can be derived from the summary this method provides, to review shape indices that have been proposed, and to report on the errors introduced using photographs of eggs at rest rather than horizontal. Abstract : Describing the range of avian egg shapes quantitatively has long been recognised as difficult. A variety of approaches has been adopted, some of which aim to capture the shape accurately and some to provide intelligible indices of shape. The objectives here are to show that a (four‐parameter) method proposed by Preston (1953) is the best option for quantifying egg shape, to provide and document an R program for applying this method to suitable photographs of eggs, to illustrate that intelligible shape indices can be derived from the summary this method provides, to review shape indices that have been proposed, and to report on the errors introduced by using photographs of eggs at rest rather than horizontal.